2018
DOI: 10.1208/s12248-018-0239-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Analysis Methods for Assessment of Pharmacodynamic Interactions Including Design Recommendations

Abstract: Quantitative evaluation of potential pharmacodynamic (PD) interactions is important in tuberculosis drug development in order to optimize Phase 2b drug selection and ultimately to define clinical combination regimens. In this work, we used simulations to (1) evaluate different analysis methods for detecting PD interactions between two hypothetical anti-tubercular drugs in in vitro time-kill experiments, and (2) provide design recommendations for evaluation of PD interactions. The model used for all simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…the concentration stimulating 20% of the of the maximum effect), 𝐼𝐶 (i.e. the concentration simulating 80% of the maximum effect) and a 'high' concentration covering the clinically relevant maximum concentrations, adapted from Chen et al (16).…”
Section: Determination Of Single Drug Effects From the Growth Inhibit...mentioning
confidence: 99%
“…the concentration stimulating 20% of the of the maximum effect), 𝐼𝐶 (i.e. the concentration simulating 80% of the maximum effect) and a 'high' concentration covering the clinically relevant maximum concentrations, adapted from Chen et al (16).…”
Section: Determination Of Single Drug Effects From the Growth Inhibit...mentioning
confidence: 99%
“…The MTP-GPDI model has been further employed to successfully evaluate and quantify the PD interactions of anti-TB drug combinations in mice [145]. Furthermore, it has been demonstrated that the GPDI model outperforms conventional methods in the evaluation of PD interactions for TB drugs [146].…”
Section: Prediction Of Human Drug-drug Interactionsmentioning
confidence: 99%
“…Optimal experimental designs for in vitro experiments for identification of PD interactions have been studied, and a rational design using only information about the EC 50 of each drug from monotherapy is used to inform the design of the PD interaction studies. 8 It is important that EBA studies are designed and analyzed in such a manner that an efficient clinical trial study is designed and analyzed with high power. Earlier work has shown that a PKPD model approach using the same underlying disease model as in this work, i.e., the MTP model, had twofold higher power for EBA studies compared with traditional studies.…”
Section: Articlementioning
confidence: 99%
“…The MTP-GPDI approach has been used to identify PD interactions both in vitro 6 and in vivo 7 and has been shown to be superior compared with other approaches for identifying PD interactions. 8 A forward translation framework for clinical exposure-response forecasting in EBA studies based on preclinical in vitro information using the MTP model has been successfully developed for rifampicin. 3 In this work, we developed a translational approach which allows for forward translation to extend the framework to predict the efficacy of the drug combination in EBA studies.…”
mentioning
confidence: 99%